Sistem Informasi Layanan Pajak Daerah Pada Badan Pengelola Pajak Dan Retribusi Daerah - Ridho Kaljannah, Muhammad; Devitra , Joni (LPPM Universitas Dinamika Bangsa, 2023)
Badan Pengelola Pajak dan Retribusi Daerah (BPPRD) Muaro Jambi is the agency used in the management of local taxes and is responsible for the implementation of the regional taxation process in Muaro Jambi Regency. In carrying out the local taxation process starting from the data collection, registration, determination to local tax processes, human resources and technology are still needed to optimize local tax revenues. For now, the taxpayer's reporting process is still being reported manually. Because the submission of reports is still manual, taxpayers must come to the office of the Muaro Jambi Regional Tax and Retribution Management Agency and fill out the form available to be calculated by the tax officer, the tax assessment must be announced. The purpose of this study is to analyze and design a local tax service information system using an object-oriented model approach using UML (Unified Modeling Language) Use Case Diagrams, Class Diagrams, Activity Diagrams, and Databases. This study resulted in a solution to the problems that existed at BPPRD Muaro Jambi, namely in the form of a regional service information system design. In this designed system, it can manage taxpayer data (restaurants, hotels and parking), manage tax reporting data, manage tax reports, view taxpayer values, view taxpayer data, provide notifications to pay taxes, and as a medium of information from the Regency BPPRD. Muaro Jambi to taxpayers so that taxpayers do not need to commute to report their taxes so that taxpayers do not need to commute to report their taxes.